Peran Perselingkuhan Dalam Menurunkan Kepercayaan Pada Hubungan Pasangan Dewasa - Aliya, Ananda Siti (Batanang : Jurnal Psikologi, 2025)
Loss of trust negatively impacts many aspects of relationship quality, including communication, intimacy, and relationship satisfaction.┬á The study also explored factors that exacerbate the impact of infidelity, such as individual personality, attachment style, and sociocultural context.┬á The results of the analysis show that cheating is not only an act that damages trust, but also triggers a negative cycle that can lead to relationship dysfunction and even separation.┬á This research highlights the importance of building and maintaining trust in adult relationships as a foundation for healthy and sustainable relationship quality. Further research is recommended to explore interventions that are effective in restoring trust and improving relationship quality after infidelity.